2016
DOI: 10.1097/ftd.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Tacrolimus and Cyclosporine in Liver Transplant Recipients Receiving 3 Direct-Acting Antivirals as Treatment for Hepatitis C Infection

Abstract: Observed data for tacrolimus and CSA in liver transplant recipients confirm that the recommended dosing strategies are valid and therapeutic levels of immunosuppression can be maintained during 3D treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
1
20
0
2
Order By: Relevance
“…Assessment of drug–drug interactions is crucial as some medications are contraindicated or not recommended during DAA therapy (e.g., high‐dose proton pump inhibitors [twice daily dosing], amiodarone [contraindicated with sofosbuvir‐inclusive regimens], and certain statins [e.g., atorvastatin], among others). Importantly, complex interactions occur between DAAs and calcineurin inhibitors . Coadministration of elbasvir/grazoprevir and cyclosporine leads to a 15‐fold increase in grazoprevir and a 2‐fold increase in elbasvir area under the concentration–time curve; this DAA regimen and immunosuppressant combination should be avoided.…”
Section: Organ Transplantation From Hcv‐viremic Donors To Hcv‐negativmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of drug–drug interactions is crucial as some medications are contraindicated or not recommended during DAA therapy (e.g., high‐dose proton pump inhibitors [twice daily dosing], amiodarone [contraindicated with sofosbuvir‐inclusive regimens], and certain statins [e.g., atorvastatin], among others). Importantly, complex interactions occur between DAAs and calcineurin inhibitors . Coadministration of elbasvir/grazoprevir and cyclosporine leads to a 15‐fold increase in grazoprevir and a 2‐fold increase in elbasvir area under the concentration–time curve; this DAA regimen and immunosuppressant combination should be avoided.…”
Section: Organ Transplantation From Hcv‐viremic Donors To Hcv‐negativmentioning
confidence: 99%
“…Importantly, complex interactions occur between DAAs and calcineurin inhibitors. (383)(384)(385)(386)(387)(388) Coadministration of elbasvir/grazoprevir and cyclosporine leads to a 15-fold increase in grazoprevir and a 2-fold increase in elbasvir area under the concentration-time curve (389) ; this DAA regimen and immunosuppressant combination should be avoided. A 40%-50% increase in tacrolimus level is predicted with coadministration of elbasvir/grazoprevir (389) ; no dosing adjustments are anticipated, but tacrolimus levels should be monitored.…”
Section: Recommendations For Daa Therapymentioning
confidence: 99%
“…There is no indication for dose adjustment in chronic kidney disease (including end‐stage renal disease), whereas additional studies have shown no requirement for dose‐adjustment in mild hepatic disease, up to and including Child class A cirrhosis. ( 27 )…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Badri et al . reported on a pharmacokinetic study that examined the interactions between ombitasvir, paritaprevir/ritonavir, and dasabuvir (SD), plus the CNIs tacrolimus and cyclosporin. They concluded that the “observed data for tacrolimus and cyclosporin in liver transplant recipients confirm that the recommended dosing strategies are valid and therapeutic levels of immunosuppression can be maintained during 3D treatment.” Bearing this in mind, we recommend that calcineurin‐inhibitor levels are closely monitored during and within the weeks following DAA therapy.…”
Section: Treatment Of Hcv Infection After Kidney Transplantationmentioning
confidence: 99%